2009
DOI: 10.1016/j.ejpoleco.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Are fiscal adjustments less successful in decentralized governments?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 35 publications
0
27
0
7
Order By: Relevance
“…and Schaltegger and Feld (2009) who find for Switzerland that less centralized cantons are more likely to conduct successful fiscal adjustments.…”
mentioning
confidence: 99%
“…and Schaltegger and Feld (2009) who find for Switzerland that less centralized cantons are more likely to conduct successful fiscal adjustments.…”
mentioning
confidence: 99%
“…A notable exception here is Schaltegger and Feld (2009), who suggest that more decentralized countries tend to be more successful in their consolidation strategies, although this result is based solely on data for the Swiss cantons. We use both descriptive statistics and simple econometrics to examine the relationship between decentralization and the numerical results achieved by the various consolidation episodes in our sample in terms of their effects on both the budget balance/GDP and the public debt/GDP ratios.…”
Section: Identificationmentioning
confidence: 71%
“…In the case of developed countries, Schaltegger and Feld (2009), in a case study of the Swiss cantons, find that fiscal centralization significantly reduces the probability of a successful fiscal consolidation, suggesting that competitive fiscal federalism may positively impact fiscal discipline. Darby et al's (2005) study of fiscal consolidations in OECD countries lends further support to the idea of the constructive participation of sub-national governments, with fiscal consolidations occurring at both central and sub-national levels.…”
mentioning
confidence: 99%
“…However, the effects of fiscal decentralization on macroeconomic stability have never been settled in empirical literature. Recently, several studies have found either no effect or a positive effect of decentralization on fiscal performance and macroeconomic stability (Schaltegger and Feld 2009, Freitag and Vatter 2008, Shah 2005, Shome 2002, Stein 1999. There is also evidence that the effects of decentralization on macroeconomic stability depend on the level of economic development and what that may represent in terms of institutions.…”
Section: Fiscal Decentralization Fiscal Sustainability and Macroecomentioning
confidence: 99%